2006
DOI: 10.1063/1.2194118
|View full text |Cite
|
Sign up to set email alerts
|

Crystalline, electronic, and magnetic structures of θ-Fe3C, χ-Fe5C2, and η-Fe2C from first principle calculation

Abstract: First principle calculations have been performed to study the crystalline, electronic, and magnetic structures of three iron-carbide systems: θ-Fe3C, χ-Fe5C2, and η-Fe2C. The Kohn-Sham equations were solved by applying the full-potential linearized augmented plane wave method. The generalized gradient approximation in the Perdew-Wang formalism was used to the exchange and correlation energy functional. The internal positions of atoms within the unit cell were optimized and the ground state properties such as l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
80
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(93 citation statements)
references
References 20 publications
13
80
0
Order By: Relevance
“…24,[62][63][64][65][66] Furthermore, our calculated lattice parameters of Fe3C agree to within ±1% of FP-LAPW values. 36,40 As discussed in a recent publication, 49 we have observed a good agreement between calculated and measured (when available) Wyckoff positions: agreement to within two significant figures is obtained for all non-symmetry-constrained Wyckoff positions between our calculations and reported experimental data.…”
Section: A Equation Of State (Eos) Of Binary Of M 3 Csupporting
confidence: 66%
See 2 more Smart Citations
“…24,[62][63][64][65][66] Furthermore, our calculated lattice parameters of Fe3C agree to within ±1% of FP-LAPW values. 36,40 As discussed in a recent publication, 49 we have observed a good agreement between calculated and measured (when available) Wyckoff positions: agreement to within two significant figures is obtained for all non-symmetry-constrained Wyckoff positions between our calculations and reported experimental data.…”
Section: A Equation Of State (Eos) Of Binary Of M 3 Csupporting
confidence: 66%
“…49 Experimentally, the EOS parameters have been determined only for Fe 3 C using diamond-and-anvil apparatus 26,5,[59][60][61] and computationally using 36,39 employing FP-LAPW and CASTEP codes. In general, our B o is higher than experimental values that could be due to the fact that experiments were conducted at room temperature or higher.…”
Section: A Equation Of State (Eos) Of Binary Of M 3 Cmentioning
confidence: 99%
See 1 more Smart Citation
“…[6] Above 720 K (450°C), it has been observed that Fe 3 C forms exclusively. [1,2] Roughly, the carbides seem to precipitate in the order g-Fe 2 C; Fe 5 C 2 ; and Fe 3 C with increasing temperature [6,7] with the appearance of -Fe 2 C preceding g-Fe 2 C: Both kinetic and thermodynamic factors could be responsible for this observation. But the predominance of each of the carbide in a definite temperature range has been attributed to the lowering of its free energy (and hence stabilization) with temperature.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] The temperature variations of magnetization of iron, Fe 4 N, and Fe 3 N can be calculated by the Weiss molecular field model. [19][20][21] The result shows that the magnetization of iron (M Fe ) is about 11.49 JT From Eq. (9), one may find that the critical nitrogen potential to form the Fe x N phase under a high magnetic field is higher than that in conventional nitriding and its value enhances with an increase in magnetic field intensity (H 0 ).…”
mentioning
confidence: 99%